Structural Analysis Of Drone Propeller Using Finite Element Analysis - John, Lorraine Pidang (Universiti Sains Malaysia, 2021)
The flight performance of a quadcopter is primarily influenced by its propellers. The maneuverability of the Quadcopter is hindered by its massive and feeble propeller. In this paper, our main goals were to investigate the relationship of thrust coefficient and rotational speed using Computational Fluid Dynamics (CFD) analysis in ANSYS Fluent. These analyses were carried out using a Navier-Stokes’s solver with Standard k-Omega turbulence model along with curvature correction where it can convert rotational power into linear propulsion, which propels the Quadcopter through space. Moreover, every propeller was unique in terms of diameter, pitch, thrust, and, most crucially, material. The solid CAD model of propeller has been designed in SolidWork Software ver2020. The created propeller design has been imported to ANSYS workbench fluid flow (fluent) and ANSYS Static Structural. The data was then transferred from the fluid flow module to static structural analysis in order to evaluate the deformation and stress caused by the pressure induced by propeller rotation at 3000 RPM and 6000 RPM. Apart from that, the materials used for the propeller throughout this research were carbon fiber reinforced plastic (CFRP) and Aluminium alloy. This was due to their lightweight characteristics and high-performance efficiency during flight. The pressure distribution demonstrated a positive pressure region on the face section and a negative region on the back section that produces the thrust generation. The propeller stress distribution was investigated, and then structural analyses were done by getting the maximum von-mises stress, maximum von-mises strain, and total propeller deformation as a consequence of this study. From the analysis, the stress distribution predicted a highly concentrated region near the hub and decreasing with the growing value of the propeller radius.